Health Consequences of Coronavirus Pandemic among Frontline Health Workers in Lagos State, Nigeria - Emakpor, R. O.; Oworu, O. O.; Emakpor, O. A. (NIU Journal of Humanities; Vol 11 No 1 (2026): NIU Journal of Humanities, Vol. 11 No. 1, March 2026DO - 10.58709/niujhu.v11i1.2459, 2026)
Coronavirus otherwise known as COVID-19 Pandemic rocked the entire world in the wake of the year 2020. The rate at which Frontline Health Workers in Lagos State were infected with Coronavirus Pandemic increased tremendously. This was as a result of exposure to infected cases, shortage of personal protective equipment (PPE) and many others. Historical research methodology was used in this study and relied on qualitative research method of data collection from primary and secondary sources. Thirty-eight Frontline Health Workers were interviewed. The study concluded that morbidity, disability and mortality were health consequences of Coronavirus Pandemic among Frontline Health workers in Lagos State, Nigeria. Keywords: Coronavirus, Frontline Health workers Health consequences, Lagos State, Pandemic.